THE EFFECTIVENESS OF ACTING PLAY SCRIPT TECHNIQUE TOWARDS STUDENTS’ SPEAKING ABILITY AT TENTH YEAR OF SMAN I LAMBUYA - Umar Umar (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study investigated The Effectiveness Of Acting Play Script Technique towards Students’ Speaking Ability At Tenth Year Of SMAN I Lambuya. The research question of this study adressed “Does the Acting Play Script Technique have significant effect towards students’ speaking ability?